The effectiveness of m-TMI-grafted-PP as a coupling agent for wood polymer composites. (October 2016) - Chauhan, Shakti; Aggarwal, Pankaj; Karmarkar, Ajay
The effectiveness of m -isopropenyl-α, α-dimethylbenzyl isocyanate-grafted-polypropylene ( m -TMI-g-PP) as a coupling agent was evaluated for wood flour filled polypropylene composites. The performance was compared with the conventionally used maleic anhydride grafted polypropylene (MAPP) coupling agent in terms of mechanical properties. Rubberwood flour filled polypropylene composites were prepared at varying proportion (1 wt% to 9 wt% of wood fibers) of m -TMI-g-PP and MAPP coupling agents. Composites with m-TMI-g-PP coupling agent exhibited consistently superior strength properties as compared to MAPP at all concentrations of coupling agents inferring that m-TMI-g-PP is a better coupling agent. About 6–9 wt% coupling agent with respect to wood fiber was found to be the optimal level of coupling agent. The effect of filler content and fiber dimension on the properties of composites with m -TMI-g-PP coupling agent was also studied. Tensile strength, flexural strength and tensile modulus increased with increasing filler content in the composites with the coupling agent. At 50% filler loading, composites with coupling agent exhibited about 50%, 78% and 270% improvement in tensile strength, flexural strength and tensile modulus, respectively, over virgin polypropylene. Fiber aspect ratio was found to have a significant effect on the tensile strength of the composites.